2015
DOI: 10.3109/15376516.2015.1045662
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin attenuates lipopolysaccharide-induced lung injury in rats

Abstract: Riboflavin (vitamin B2) is an easily absorbed micronutrient with a key role in maintaining health in humans and animals. It is the central component of the cofactors flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN) and is therefore required by all flavoproteins. Riboflavin also works as an antioxidant by scavenging free radicals. The present study was designed to evaluate the effects of riboflavin against acute lungs injury induced by the administration of a single intranasal dose (20 μg/rat) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Decreased GSH levels have been reported to increase by riboflavin treatment in carbon tetrachloride-induced hepatotoxicity, stroke and lipopolysaccharide-induced lung injury models. [16][17][18]. Our data are consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Decreased GSH levels have been reported to increase by riboflavin treatment in carbon tetrachloride-induced hepatotoxicity, stroke and lipopolysaccharide-induced lung injury models. [16][17][18]. Our data are consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Our study indicated that riboflavin treatment reduces renal MDA levels through its antioxidative properties. It has been previously shown that riboflavin treatment decreased MDA levels in liver [16], brain [17] and lung [18] and thus protected against carbon tetrachloride-induced hepatotoxicity, stroke and lipopolysaccharideinduced lung injury respectively. Therefore, the reduction of MDA levels presented here probably contributed in great sense to the inhibition of I/R events in kidney tissues.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that RF reduced the hepatocellular injury and hepatotoxicity induced by LPS through elevation of malondialdehyde (MDA) level and myeloperoxidase (MPO) activity, whereas a marked decrease in GSH content, GR and glutathione peroxidase (GPx) activity. Moreover, expression of inducible nitric oxide synthase (iNOS) and catalase (CAT) gene expression was improved via RF administration [45]. In addition, RF reduces mortality rates through the reduction of the expression and release of high-mobility group protein B1 (HMGB1); however, the effect of RF was time-dependent [46].…”
Section: Immune Systemmentioning
confidence: 99%
“…More recently, it was reported that administration of soymilk fermented by the RF‐producing Lactobacillus plantarum strain to mice showed anti‐inflammatory effects by lowering microbial translocation to liver and decreasing cytokine levels in intestinal fluids in a trinitrobenzene sulfonic acid‐induced intestinal inflammation model . Furthermore, RF caused a protective effect by reversing cellular changes such as interstitial edema, haemorrhage and polymorphonuclear leukocyte infiltration against lipopolysaccharide‐induced acute lung injury . In addition, RF has been shown to reduce proinflammatory activity of macrophages and exert anti‐inflammatory effects by inhibiting nuclear factor (NF)‐κB activation .…”
Section: Introductionmentioning
confidence: 99%